HARMONI AGUNG DAN EKSISTENSI MANUSIA DALAM NEO-KONGHUCUISME DAN PAUL RICOEUR - Selatang, Fabianus (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
The purpose of this paper is to find the meeting point of Neo-Confucianphilosophy concept of Great Harmony with the philosophy of Paul Ricoeurabout human existence. The notion of Great Harmony in the Neo-Kunghucuismphilosophy will be explored in the thinking of Chou Tun-I, Cheng and ChuHsi philosophers. These three philosophers initiated the concept of GreatHarmony by displaying different characteristics and characteristics. Thoughthey are different, , the direction of the three talks leads the reader to discoverthe meaning and meaning of human existence which Paul Recoeur referredto as a hermeneutic creature. In an attempt to elaborate the idea of GreatHarmony and human existence, the author uses the hermeneutic method. Theconclusion is that human existence has a double meaning (plural) and notsingular. This is where the importance of language hermeneutics to interprethuman existence, especially in relation to God as the Supreme Reality.